Eye tracking-based dual task in rehabilitation of motor and cognitive function in post-stroke patients: a literature review - Marcella Sugianto; Yuda Zhou; Jifang Qiu (Bulletin of Faculty of Physical Therapy)
Abstract Eye-tracking technologies have emerged as a transformative tool in the rehabilitation and assessment of stroke patients, offering innovative approaches to understanding visual attention and enhancing communicative abilities. Stroke often leads to significant impairments in motor function, cognitive processing, and visual fields, necessitating the development of effective rehabilitation strategies. Eye-tracking, which involves the measurement of eye position and movement, holds promise in both clinical and therapeutic contexts for these patients. Recently, the world of rehabilitation has been revolutionized by groundbreaking methods that utilize eye tracking technology. To address motor dysfunction and/or cognitive dysfunction, these innovative approaches are transforming traditional dual-task rehabilitation methods for patients with stroke. Until recently, eye tracking has been used as an early detection tool for cognitive impairment, while some stroke patients have cognitive impairments, and we tried to find eye tracking rehabilitation tools for stroke patients with motor-cognitive impairments. With the help of past research papers and results, it does show that eye tracking has a promising future in motor-cognitive dual-task rehabilitation for stroke patients with motor-cognitive impairment. Background. There’s so many ways of rehabilitating stroke patients, and lately the eye tracking technology is booming for early detection of cognitive impairments, such as autistic or mild cognitive impairments. The aim of this review is to summarize the eye tracking-based dual-tasks that can be applied to stroke patients. Eye-tracking technology have been used recently and is relatively new for stroke patients, and less research has been conducted. The present review addresses whether the effectiveness of the eye-tracking mechanism in the rehabilitation of post-stroke patients with motor dysfunction can be validated.